2018
DOI: 10.1371/journal.pntd.0006293
|View full text |Cite
|
Sign up to set email alerts
|

A rabies lesson improves rabies knowledge amongst primary school children in Zomba, Malawi

Abstract: Rabies is an important neglected disease, which kills around 59,000 people a year. Over a third of these deaths are in children less than 15 years of age. Almost all human rabies deaths in Africa and Asia are due to bites from infected dogs. Despite the high efficacy of current rabies vaccines, awareness about rabies preventive healthcare is often low in endemic areas. It is therefore common for educational initiatives to be conducted in conjunction with other rabies control activities such as mass dog vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…Improvement in rabies awareness through the development of education campaigns has been recognised as a key factor in order to control the infection [5]. The delivery of these activities has been proven beneficial not only to provide the community with accurate information on disease prevention, but to improve their attitude concerning dog vaccination and engagement with rabies surveillance [13,45,46]. A similar regression analysis also showed that education was positively associated with the owner's intention to vaccinate their dog [44].…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Improvement in rabies awareness through the development of education campaigns has been recognised as a key factor in order to control the infection [5]. The delivery of these activities has been proven beneficial not only to provide the community with accurate information on disease prevention, but to improve their attitude concerning dog vaccination and engagement with rabies surveillance [13,45,46]. A similar regression analysis also showed that education was positively associated with the owner's intention to vaccinate their dog [44].…”
Section: Variablementioning
confidence: 99%
“…In 2016, the campaign was expanded to the neighbouring Zomba and Chiradzulu districts vaccinating nearly 90,000 dogs [10]. Alongside vaccination, rabies educational campaigns were conducted in schools in the three districts, which has been shown to effectively increase the knowledge of rabies in primary school children [13].…”
Section: Introductionmentioning
confidence: 99%
“…10 Studies conducted in school children have shown improvements in knowledge, attitudes and practices towards rabies management among them. 11,12 This study conducted in Malda District, West Bengal can improve the awareness about rabies in children and provide better medical care.…”
Section: Discussionmentioning
confidence: 99%
“…Periodic checks through co-supervision by management staff in the field during mass vaccination campaigns were used to correct any variation from standard operating procedures. Further information about the training protocol for education officers and retention of rabies understanding was described by Bailey et al (2018) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%